(untitled) (Vallis Aurea, 2020)
This paper systematically deals with the matter of nomotechnical rules of drafting legal regulations with special reference to essential preconditions of drafting legal regulations. The national sources of law are studied relating to the procedure of drafting legal regulations, which arise from the Rules of Procedure of the Croatian Parliament and what possibilities the prescribed and unique methodological-nomotechnical rules have. The emphasis is on determining the essential preconditions for the enaction and drafting of legal regulations, and on the advantages that contribute to a better drafting of legal regulations in the national system. This is a very interesting topic since the so-called nomotechnical rules did not appear in scientific terms until the 19th century and are still evolving. The nomotechnical rules institute plays a very important role as a foundation of legal certainty.